Analisis Upaya Guru dalam Membangun Motivasi Belajar Siswa di SDN 2 Bone - Miranda Ruchban; Yulanti S. Mooduto; Andi Nur Syarif Hidayatullah; Thamrin A. Kum (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze teachers’ efforts in fostering students’ learning motivation at SDN 2 Bone. The research employed a qualitative approach with a phenomenological design to gain an in-depth understanding of teachers’ experiences and practices in the learning process. The research subjects consisted of the principal, teachers of grades IV, V, and VI, and students from each grade, selected purposively. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings reveal that teachers foster students’ learning motivation through several key strategies: connecting learning materials to students’ real-life experiences, demonstrating enthusiasm in teaching, creating a pleasant and non-threatening learning environment, building psychologically safe classrooms, utilizing evaluation as a reflective tool, and providing opportunities for students to express their potential. These strategies effectively enhance students’ engagement, confidence, and learning enthusiasm. This study concludes that students’ learning motivation is developed through consistent, student-centered instructional practices. The findings provide practical implications for developing more effective teaching strategies to enhance learning motivation in primary education.